The influence of board, CEO, and audit committee chairman busyness on the value relevance of accounting information in Saudi listed firms - Abdulrahman Alomair; Abdulaziz S. Al Naim (PLoS ONE, 2025)
This study investigates the impact of board, CEO, and audit committee chairman busyness on the value relevance of accounting information in Saudi listed firms from 2018 to 2022. Utilizing a data of 125 Saudi firms, the research investigates how the busyness of these key governance figures influences the relevance of earnings per share (EPS) and book value per share (BVPS). The findings reveal that board and audit committee chairman busyness significantly enhance the value relevance of EPS, suggesting that their broader networks and strategic oversight improve financial reporting. Conversely, CEO busyness negatively affects the value relevance of BVPS, indicating that divided attention and reduced managerial oversight hinder performance monitoring. These results underscore the dual roles of governance figures and their influence on financial reporting quality. These results highlight the dual effects of governance busyness on financial reporting quality. The study provides novel insights into an emerging market context, offering practical recommendations for policymakers and corporate leaders in line with Saudi Arabia’s Vision 2030. It emphasizes the need for regulatory frameworks to manage director workloads, ensuring enhanced financial reporting and governance effectiveness.